Academic entitlement: Its personality and general mental ability correlates, and academic consequences. (November 2016) - Bonaccio, Silvia; Reeve, Charlie L.; Lyerly, Jordan
Abstract: Academic entitlement, composed of entitled expectations and externalized responsibility, is thought to be an individual difference construct reflecting an expectation of academic success without need for taking personal responsibility by exerting the necessary effort required. This field study uses both cross-sectional and longitudinal data collected in a real classroom setting to test the degree to which general mental ability and personality traits predict academic entitlement. This study further tests the degree to which academic entitlement incrementally predicts final course grades in real college courses, net ability and personality. Results show that externalized responsibility predicts final course grades when considered alone, but does not do so when other predictors of academic success, such as personality traits and general mental ability, are considered. The results are discussed in light of the emerging literature on academic entitlement. Implications for higher education are discussed. Highlights: Academic entitlement involves entitled expectations and externalized responsibility. Agreeableness and conscientiousness negatively predict entitled expectations. Both entitlement dimensions were negatively related to final course grades. When accounting for ability and personality, entitlement no longer uniquely predicted grades.